Penerapan Analisis Semiotika Roland Barthes Dalam Menemukan Pesan Dakwah Pada Buletin Citra Diri Edisi 86 Juli 2019 - Salma Rofidah; Henri Peranginangin; Mahmudah Fitriyah, Z.A (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
The usage of printed media is a sufficiently effective and efficient da’wah way. The message content contained in certain printed media will be understood well by the reader if using suitable method. This research aimed to find out (1) what is the da’wah message obtained in Buletin Citra Diri 86 Edition July 2019, (2) what da’wah message is dominant in Buletin Citra Diri 86 Edition July 2019 by using semiotics analysis of Roland Barthes. The type of research used was library research with qualitative interpretative delivery. The text which contained da’wah message in Buletin Citra Diri 86 Edition July 2019 was analyzed by using semiotics theory of Roland Barthes with two order of signification and breaking the myth in it. The research results show that the message contents contained in Buletin Citra Diri 86 Edition July 2019 are such as (a) aqidah message: the belief towards Allah SWT; and (b) akhlak; taqwa, ikhlas, intention just cause of Allah Ta’ala, the best planner, work hard, and not considering anything as an ally of Allah SWT. The dominant message in the bulletin is akhlak message.